The Development of a Process Control System for the Production of Partially Reducing Nickel Oxide in a Tubular Rotary Kiln - V. Sharikov, Yu.; Liu, C (International Journal of Engineering and Technology, 2018)
This article describes the results of a control system development by the process of nickel oxide reducing to obtain partially reducing nickel oxide (PRNO) in a tubular rotary kiln (TRK). The purpose of the recovery in TRK is to obtain an enlarged, maximally recovered product before the anode electric fusion, since such an electrically conductive product, as partially reduced nickel oxide (PRNO), allows to reduce the electricity and reducing agent consumption during the process of electric smelting, which is economically advantageous. TRK is an object with distributed parameters. The reducing product quality is determined by the temperature profile along a kiln length. The development of a temperature profile control system is required, ensuring the receipt of a specified quality product for the objects with distributed parameters. The cell model was used in the work, corresponding to the 5 technological zones of the process, the dynamic model of the object was constructed and the dynamic behavior of the object was studied with step perturbations and the use of 3 different control systems. The analysis of the obtained data made it possible to establish that the best control results are obtained by a fuzzy regulator use.Â